Collider aspects of flavor physics at high Q - Lari, T; Pape, L; Porod, W; Aguilar-Saavedra, J; Allanach, B; Burdman, G; Castro, N; Klasen, M; Krasnikov, N; Krauss, F; Moortgat, F; Polesello, G; et al. (2008)
This chapter of the 'Flavor in the era of LHC' workshop report discusses flavor-related issues in the production and decays of heavy states at the LHC at high momentum transfer Q, both from the experimental and the theoretical perspective. We review top quark physics, and discuss the flavor aspects of several extensions of the standard model, such as supersymmetry, little Higgs models or models with extra dimensions. This includes discovery aspects, as well as the measurement of several properties of these heavy states. We also present publicly available computational tools related to this topic. © Springer-Verlag / Società Italiana di Fisica 2008.